Information Technology in the Social Media Application - S Luckyardi; D J Kusnadi; F Santanu; R N Subandrio (Peneliti.net, 2021)
The purpose of this study is to describe and analyze the impact of information technology on social media. It focuses on the use of social used for business. This study used the descriptive qualitative method. Data collection techniques such as interviews, observation of non-participation, and internet searching. This study shows that information technology (IT), mainly social media, influences consumers who want to do a transaction and buy a product. Currently, technology is overgrowing, encouraging a person to use social media to conduct transactions and buy a product because it can facilitate entrepreneurs in developing their business